A Video-Conferencing English–Spanish eTandem Exchange: Negotiated Interaction and Acquisition. (20th May 2021) - Arellano-Soto, German; Parks, Susan
Abstract : This study analyzed eTandem video-conferencing exchanges between five pairs of university students of English as a foreign language (EFL) and Spanish as a foreign language (SFL). The exchanges, which involved discussion of seven tasks, took place on a weekly basis. Drawing on an interactionist perspective (Ellis et al., 2001a; Loewen, 2005), the study explored the impact of incidental noticing on subsequent language learning. Data were collected from two sources: transcripts of all the video-conferencing sessions and immediate and delayed post-tests. Drawing on Loewen's (2005) framework of analysis, the transcripts revealed that students generated a total of 915 focus-on-form episodes (FFEs). As measured by the post-tests, participants recalled over half of the targeted FFE linguistic items. In contrast to previous studies (Loewen, 2005; Shekary & Tahririan, 2006), where successful uptake was a predictor for L2 learning, the present study revealed that the only significant predictor was deferred timing. More generally, the present study supports the claim that eTandem video-conferencing is a useful activity for promoting L2 acquisition.